Design of Science Process Skill-Based Intertextual Learning on Reaction Kinetics Concept - Jihan Assyifa Fatihah; Tuszie Widhiyanti; Sri Mulyani; Wiji Wiji; Galuh Yuliani (Jurnal Tadris Kimiya, 2022)
The study aims to design an intertextual learning strategy with Predict-observe-explain (POE) to develop students' science process skills. The research method is Research and Development (R&D) consist of material analysis, developing indicators of science process skills, and developing learning designs. The learning design was validated by five experts. Based on experts’ suggestion, intertextual-based learning activities involving three levels of chemical representation with POE learning steps to build the concept of the effect of the nature of the reactant and catalyst on reaction rates and develop students' science process skills. The strategy consists of five phenomena which are followed by three experiments and two videos as observation tools for the student. The explanation stages are guided by sets of guiding questions that involve multi-representation levels in that explanation. The product of this research is expected to be used as an alternative learning strategy that can be used by teachers to minimize the possibility of misconceptions that occur, increase mastery of concepts, and students' science process skills.